Fostering Microfinance Access To Sari-Sari Stores In The City Of San Fernando, La Union - Eirah B. Cañero; John Michael L. Abubo; Rachelle D. Garbo; Lealyn A. Jacosalem; Edlyn Jane S. Tango (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
Microfinance institutions empower sari-sari store owners to achieve selfsufficiency by providing access to financial services, including business loans, which foster growth and financial stability. The study was conducted to determine the extent of access to microfinance of sari-sari stores and their financial performance, and the significant relationship between the extent of access to microfinance and financial performance. Data from 22 sari-sari stores were gathered using a validated questionnaire and were analyzed using median, mean and Spearman’s Rho. The respondents have agreed that microfinance services were highly accessible in terms of interest rates, loan repayment period and financial innovation. Findings revealed that only interest rates and loan repayment periods under extent of access to microfinance have a significant relationship with profitability. While a factor under financial innovation, specifically in providing sufficient grace period in case of difficulties significantly affect the stability.